2004
DOI: 10.1021/ma035674j
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Polyamide by Reactive Blending. 1. Effect of the Reactive Diblock Composition

Abstract: Reactive blending of phthalic anhydride end-capped polystyrene-b-polyisoprene diblock (PSb-PIP-anh) with 80 wt % of polyamide 12 (PA12) results in the very rapid formation of a PS-b-PIP-b-PA triblock copolymer, which self-assembles with formation of characteristic nanoobjects, within the polyamide matrix. For instance, a vesicular nanostructure is formed in the particular case of a symmetric, lamellarforming diblock copolymer. This morphology actually complies with the lower curvature possible for ABC lamellae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…To overcome this problem, a core–shell morphology, which consists of a rigid core and a soft shell, rather than pure low modulus modifiers, has been used to impart a substantial toughening to the matrix while keeping rigidity reasonably high. Generally, the formation of core–shell structure in toughened PA6 blends was by melt compounding PA6 with rubber and a stiff polymer, or with prior‐prepared end‐functional block copolymers . The difficulty is the formation of effective core–shell structures due to the low diffusion rates of viscous rubber in the ternary blend and the micellization or self‐assembly effect of block copolymers in the copolymer toughened system.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, a core–shell morphology, which consists of a rigid core and a soft shell, rather than pure low modulus modifiers, has been used to impart a substantial toughening to the matrix while keeping rigidity reasonably high. Generally, the formation of core–shell structure in toughened PA6 blends was by melt compounding PA6 with rubber and a stiff polymer, or with prior‐prepared end‐functional block copolymers . The difficulty is the formation of effective core–shell structures due to the low diffusion rates of viscous rubber in the ternary blend and the micellization or self‐assembly effect of block copolymers in the copolymer toughened system.…”
Section: Introductionmentioning
confidence: 99%
“…Microphase‐separated block copolymers [2–4] and polymer nanocomposites with homogeneously dispersed nanofillers [5–9] are two typical well‐investigated heterogeneous transparent polymeric materials. On the other hand, considerable attention has also been paid to the blending of a homopolymer with a block copolymer containing blocks similar to the homopolymer [10–15]. It was shown that the one block of the copolymer can be incorporated into the homopolymer and the other blocks form a nanostructured phase due to the microphase separation.…”
Section: Introductionmentioning
confidence: 99%
“…31 One key difference that may explain our results is that the amine on the p-amino styrene monomer was an aniline, which does not react as quickly as a primary aliphatic amine. [77][78][79] With slower coupling rates, the interface cannot be stabilized as rapidly, leading to slightly larger final domain sizes.…”
Section: Rheologymentioning
confidence: 99%